2004
DOI: 10.1002/ijc.20709
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive smoking and breast cancer risk in middle‐aged Japanese women

Abstract: To examine the hypothesis that tobacco smoke is associated with the risk of female breast cancer, we estimated the relative risks of active and passive smoke in middle-aged Japanese women in a population-based prospective study. The cohort consisted of residents in 4 public health center areas, aged 40 to 59 years. A self-administered questionnaire survey was conducted in 1990. This analysis included 21,805 subjects, 180 of whom had developed breast cancer by December 31, 1999. When the reference was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 34 publications
3
70
2
1
Order By: Relevance
“…In the present study, only early exposure in the reproductive period could be a breast cancer risk. The risk of passive smoke in premenopausal women in this study was also consistent with other studies (Hanaoka et al, 2005;Johnson et al, 2011). Human breast tissue is sensitive to environmental carcinogens in the premenopausal period, during periods of rapid cell proliferation during puberty when that differentiation is incomplete, and when complete cellular differentiation is never achieved in nulliparity women (Reynolds, 2013).…”
Section: And the Statistical Comparison Between Two Groupssupporting
confidence: 91%
“…In the present study, only early exposure in the reproductive period could be a breast cancer risk. The risk of passive smoke in premenopausal women in this study was also consistent with other studies (Hanaoka et al, 2005;Johnson et al, 2011). Human breast tissue is sensitive to environmental carcinogens in the premenopausal period, during periods of rapid cell proliferation during puberty when that differentiation is incomplete, and when complete cellular differentiation is never achieved in nulliparity women (Reynolds, 2013).…”
Section: And the Statistical Comparison Between Two Groupssupporting
confidence: 91%
“…39 Consistent with a previous study, 4 we found little evidence of a statistical interaction between smoking status and alcohol intake on the development of breast cancer, although we previously reported a substantial association between smoking and premenopausal breast cancer risk in our cohort. 67 The major strength of our study is its prospective population-based cohort design. Our large sample size and repeated measurement of exposure information over a long follow-up period likely aided the precision of our risk estimate.…”
Section: Discussionmentioning
confidence: 99%
“…While the results from some studies are unconvincing (Pirie et al, 2008;Anderson et al, 2012), the numerous studies suggested an increase in risk with exposure to passive tobacco smoke (Kropp and ChangClaude, 2002;Slattery et al, 2008;Luo et al, 2011). This association has been stronger for premenopausal compared to postmenopausal women (Hanaoka et al, 2005;Slattery et al, 2008). The purpose of this study was to investigate the association between cigarette smoking and breast cancer risk.…”
Section: Introductionmentioning
confidence: 95%